Feasibility of Printed Optical Waveguides Over the Entire Process Chain by OPTAVER - Hoffmann, Gerd Albert; Wienke, Alexander; Kaierle, Stefan; Overmeyer, Ludger; Hamjah, Mohd Khairulamzari; Reitberger, Thomas; Zeitler, Jochen; Franke, Jörg; Lorenz, Lukas; Bock, Karlheinz; Backhaus, Carsten; Loosen, Florian; et al. (Springer International Publishing, 2022)
The integration of the knowledge of different engineering disciplines to build a three-dimensional optical short-range interconnect system is the core of this book. For this purpose, the physical and technological principles of optical technologies have to be considered. The focus here is on optical transmission technology. Attenuation, the propagation of optical signals, the construction of printed optical waveguides and their manufacturing processes play a special role. Likewise, product development methods of technical systems are a related field; since up to now, especially for 3D-Opto-MID, no adequate methodology exists. Analogies to mechatronic systems and their sub-processes do exist, but these have to be evaluated and expanded with regard to the new optomechatronic components.
CRIS-Team Scopus Importer:2024-12-16